2006
DOI: 10.1111/j.1476-4431.2006.00184.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluid therapy for the traumatized patient

Abstract: Objective: To review the rationale behind and experiences with traditional and newly evolving concepts of fluid therapy in the traumatized patient, and to review conventional and novel fluid preparations for use in trauma resuscitation. Data sources: Human and veterinary clinical and research studies. Human data synthesis: Current treatment guidelines recommend aggressive fluid resuscitation with lactated ringers solution (LRS) or saline as optimum management of hemorrhagic shock in trauma, regardless of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 209 publications
(659 reference statements)
1
21
0
3
Order By: Relevance
“…Similarly, in vitro studies in dogs demonstrated that both mannitol and HTS have negative effects on coagulation in a dose-dependent fashion, although in vivo studies in dogs in a clinical setting are lacking [16, 17]. As a result, current guidelines for osmotherapy in dogs with ICH are largely extrapolated from experimental data and human literature [18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in vitro studies in dogs demonstrated that both mannitol and HTS have negative effects on coagulation in a dose-dependent fashion, although in vivo studies in dogs in a clinical setting are lacking [16, 17]. As a result, current guidelines for osmotherapy in dogs with ICH are largely extrapolated from experimental data and human literature [18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] It is also important to recognize that once a "reasonable" amount has been administered but the hypotension has not resolved, additional fluids are unlikely to provide benefit and may be harmful. This includes causes of absolute (e.g., hemorrhage) or relative (e.g., obstruction or vasodilation) hypovolemia and typically not primary causes of cardiac dysfunction.…”
Section: Fluid Resuscitationmentioning
confidence: 99%
“…A própria definição do choque circulatório, como uma redução crítica na perfusão tecidual por anormalidade do sistema circulatório, já se transforma em instrumento operacional para elaboração do seu tratamento, não existindo nenhum agente isolado capaz de revertê-lo (MARSON et al, 1998;DRIESSEN;BRAINARD, 2006). Dessa forma, o tratamento do choque circulatório é meramente de suporte.…”
Section: Tratamentounclassified
“…As soluções cristalóides contêm um ânion tamponante, seja o acetato ou o lactato. Aparentemente, as soluções contendo acetato são mais adequadas para o restabelecimento da volemia nos estados de choque, pois a capacidade do organismo metabolizar lactato pode estar diminuída nos estados de choque, independente da causa (HJELMQVIST, 2000;DRIESSEN;BRAINARD, 2006). O volume de fluido a ser administrado é estimado com base no déficit para reposição, requerimentos de manutenção e perdas futuras antecipadas.…”
Section: Fluidoterapiaunclassified
See 1 more Smart Citation